2009
DOI: 10.2105/ajph.2008.153205
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patrons' Meal Selections Through the Use of Point-of-Selection Nutrition Labels

Abstract: Use of nutrition labels reduced the average energy content of entrées purchased without reducing overall sales. These results provide support for strengthening the nutrition labeling policy in food-service operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
132
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(142 citation statements)
references
References 19 publications
7
132
0
3
Order By: Relevance
“…Some studies report no change [23][24][25][26] or increased calorie intake of ordered items 27 associated with calorie labeling on menus, whereas other studies indicate a significant decrease in calorie levels. [28][29][30][31][32][33] Calorie labeling on menus can take several forms. Regulations in many jurisdictions require only the calorie numbers; alternatively, a descriptive statement can accompany numeric information, such as the health statement from the FDA proposed regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report no change [23][24][25][26] or increased calorie intake of ordered items 27 associated with calorie labeling on menus, whereas other studies indicate a significant decrease in calorie levels. [28][29][30][31][32][33] Calorie labeling on menus can take several forms. Regulations in many jurisdictions require only the calorie numbers; alternatively, a descriptive statement can accompany numeric information, such as the health statement from the FDA proposed regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the FDA has been thorough and thoughtful in the solicitation and consideration of stakeholder comments, it remains a problematic challenge, because published research to date has produced inconsistent findings about the ideal format and overall efficacy of calorie postings in restaurants. 2,5,[6][7][8][9][10][11][12][13][14][15][16][17][18] For example, two recent studies in adjoining counties in Washington State produced inconclusive results. Pulos and Leng 17 evaluated the calorie content of meals ordered before and after menu labeling laws were instituted in Pierce County (population 814,600), revealing significant differences in food purchasing behavior with a reduction in calories purchased after the menu-posting legislation.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, students in a college dining hall decreased the caloric content of their meal selections when calorie labels were displayed and began increasing the caloric content soon after calorie labels were removed [26]. Previous studies where 9% and 14.5% of participants used calorie labels to make ordering decisions showed no significant overall difference in calories purchased after viewing menu labels [40,41].…”
Section: Discussionmentioning
confidence: 90%
“…Various methods have been utilized to collect the data with results spread across the board. Studies have shown that the majority of consumers support the menu labels [18-21]; however, whether or not they will actually use them to decrease the caloric content of their restaurant meals is more controversial.Studies conducted in college dining halls have had generally consistent results-a moderate number of college students want nutrition information available and/or use posted nutrition information to make lower-calorie meal selections [22][23][24][25][26]. One study reported two-thirds of the freshman respondents were aware of the food labels in the dining hall, while one-third actually used them to make meal selections (actual change in calories purchased was not measured) [23].…”
mentioning
confidence: 99%